دراسة تحليلية اقتصادية لزراعة الكيوي في محافظة اللاذقية - درويش, نضال; مهنا, رنا (Latakia University Journal -Biological Sciences Series, 2013)
تعد زراعة الكيوي من الزراعات البديلة، والحديثة، ذات المستقبل الواعد في الساحل السوري بشكل عام، ومحافظة اللاذقية بشكل خاص، نظراً لتأقلمه مع الظروف البيئية والطبيعية المحلية، وارتفاع مردوده الاقتصادي، لذا فإن تطوير وتوسيع الزراعات البديلة، ومنها الكيوي، كان من أهم الأهداف المحددة لاستراتيجية التنمية الزراعية المستقبلية في سورية. وقد سعى هذا البحث إلى تحقيق الأهداف الآتية: أ‌- حساب التكاليف الإنتاجية لإنتاج الكيوي في محافظة اللاذقية، وتحليلها. ب‌- التقييم الاقتصادي لزراعة الكيوي في محافظة اللاذقية, من خلال حساب مؤشرات التحليل الاقتصادي لهذه الزراعة. وقد تبين من خلال دراسة مؤشرات الكفاءة الاقتصادية لإنتاج الكيوي في محافظة اللاذقية أن: متوسط صافي الدخل المزرعي في الدونم الواحد بلغ (767727.09) ل.س خلال (2001 - 2010)م. متوسط الربح المحقق في الدونم الواحد يعادل (751909.83) ل.س خلال (2001-2010)م. متوسط الهامش الإجمالي في الدونم الواحد يعادل (877661.41) ل.س خلال (2001-2010)م. الكفاءة الإنتاجية المزرعية بلغت (4.23). الكفاءة الاقتصادية الإجمالية بلغت (3.21). The cultivation of kiwi is one of the modern alternative cultivations which has a promising future in the Syrian coast in general, and in the governorate of Lattakia in particular, due to its great adaptability to the local environmental and natural conditions in addition to its high economic returns. Therefore, developing and expanding the alternative cultivations such as the kiwi has been regarded as one of the most important goals set for the future agricultural developmental strategies in Syria. This research has sought to achieve the following objectives: A-Studying the kiwi production costs and analyzing them in Syria. B- The economic assessment of the kiwi cultivation in Lattakia through studying the economic analysis indicators of this agriculture. The study showed that: 1. The net farming revenue per one dunum reached (767727.09) s.p/ten years. 2. Each dunum made a profit of (751909.83) s.p/ten years. 3. The gross margin per one dunum is (877661.41) s.p/ten years. 4. The farming productivity efficiency reached (4.23). 5. The overall economic efficiency reached (3.21).